Construction of multi-enzyme cascade biomimetic carbon sequestration system based on photocatalytic coenzyme NADH regeneration. (August 2020) - Zhou, Junhui; Yu, Senshen; Kang, Helong; He, Rui; Ning, Yuxin; Yu, Yingyue; Wang, Meng; Chen, Biqiang
Abstract: CO2 is one of the main gases leading to the greenhouse effect. The use of a multi-enzyme biological carbon capture and utilization method can reduce the concentration of CO2 . However, most oxidoreductases require NADH as a coenzyme, which is too expensive to afford for most situation. In this research, NADH was regenerated using photocatalysis and CO2 was converted to formaldehyde by FateDH and FaldDH gradually. TCPP and ZIF-8 were successfully combined to construct a photocatalytic multi-enzyme cascade biomimetic carbon sequestration system for the first time. TCPP was used as the photocatalyst and ZIF-8 was used as the multi-enzyme immobilized carrier for FateDH and FaldDH. The TCPP content, material dosage, pH of reaction solution and the ratio of the two enzymes were optimized in this study. The results indicated that when reacting under visible light for 3 h, using 1 mg/mL 3% TCPP @ZIF-8 at pH 8.0 PBS condition, it has the highest NADH reduction rate, reaching 75.04%. It was also found that when FateDH: FaldDH = 2:1, the formaldehyde yield can reach up to 7.74 μM. And the formaldehyde conversion rate reached 77.37%. In addition, this composite system retained 52.93% of residual activity after 10 batches of re-use. Highlights: A photocatalytic multi-enzyme cascade carbon sequestration system was constructed. Coupled TCPP and ZIF-8 were used for regeneration of NADH with a yeild of 75.04%. FateDH and FaldDH were immobilized to produce HCHO from CO2 with a yeild of 77.37%. The carbon sequestration system can be reused for 10 times.